Disruption of Mks1 localization to the mother centriole causes cilia defects and developmental malformations in Meckel-Gruber syndrome - Cheng Cui; Bishwanath Chatterjee; Deanne Francis; Qing Yu; Jovenal T. SanAgustin; Richard Francis; Terry Tansey; Charisse Henry; Baolin Wang; Bethan Lemley; Gregory J. Pazour; Cecilia W. Lo (The Company of Biologists, 2011)
SUMMARY Meckel-Gruber syndrome (MKS) is a recessive disorder resulting in multiple birth defects that are associated with mutations affecting ciliogenesis. We recovered a mouse mutant with a mutation in the Mks1 gene (Mks1del64-323) that caused a 260-amino-acid deletion spanning nine amino acids in the B9 domain, a protein motif with unknown function conserved in two other basal body proteins. We showed that, in wild-type cells, Mks1 was localized to the mother centriole from which the cilium was generated. However, in mutant Mks1del64-323 cells, Mks1 was not localized to the centriole, even though it maintained a punctate distribution. Resembling MKS patients, Mks1 mutants had craniofacial defects, polydactyly, congenital heart defects, polycystic kidneys and randomized left-right patterning. These defects reflected disturbance of functions subserved by motile and non-motile cilia. In the kidney, glomerular and tubule cysts were observed along with short cilia, and cilia were reduced in number to a near-complete loss. Underlying the left-right patterning defects were fewer and shorter nodal cilia, and analysis with fluorescent beads showed no directional flow at the embryonic node. In the cochlea, the stereocilia were mal-patterned, with the kinocilia being abnormally positioned. Together, these defects suggested disruption of planar cell polarity, which is known to regulate node, kidney and cochlea development. In addition, we also showed that Shh signaling was disrupted. Thus, in the neural tube, the floor plate was not specified posteriorly even as expression of the Shh mediator Gli2 increased. By contrast, the Shh signaling domain was expanded in the anterior neural tube and anterior limb bud, consistent with reduced Gli3-repressor (Gli3R) function. The latter probably accounted for the preaxial digit duplication exhibited by the Mks1del64-323 mutants. Overall, these findings indicate that centriole localization of Mks1 is required for ciliogenesis of motile and non-motile cilia, but not for centriole assembly. On the basis of these results, we hypothesize a role for the B9 domain in mother centriole targeting, a possibility that warrants further future investigations.